Tolerância e resposta imune à vacina tríplice acelular do adulto (dTpa) em adolescentes infectados pelo vírus da imunodeficiência humana (HIV) - Spina, Fernanda Garcia [UNIFESP] (2016)
Background: Despite the decay in morbidity and mortality among HIV-infected children and adolescents, they still have a higher susceptibility to infectious diseases and a reduced immune response to vaccination. However, knowledge on immune response to vaccine antigens is scarce in HIV-infected adolescents. Objectives: To evaluate the tolerability, antibody persistence and the humoral and cellular response after Tdap in HIV-infected and in healthy adolescents, in comparison to healthy adolescents. Methodology: This was a controlled non-blind clinical trial with HIV-infected adolescents (HIV, n=30) and healthy controls (CONTROL, n=30) who had received primary vaccination scheme (3 doses) and at least one booster dose of tetanus diphtheria whole cell pertussis vaccine and who had at least a 3 year-interval since the last vaccine dose. Individuals from HIV group had to have at least 200 CD4+ T cells/mm3. Pregnancy was an exclusion criterion for both groups. One Tdap was administered and adolescents filled in a form to report adverse events. Three blood samples were collected: immediately bofore vaccination (day 0) and after 14 (day 14) e 28 days (day 28). Lymphocyte subset immunophenotyping with flow cytometry was performed on day 0. Humoral immunity to tetanus, diphtheria and pertussis toxin was assessed by ELISA. In vitro culture was performed with whole blood stimulated with tetanus toxoid, Bordetella pertussis or medium. Supernatants were collected after 7 days, kept frozen and subsequently assessed for cytokines secretion by xMAP-Luminex platform. This project was approved by the Ethics Committee and all patients and guardians signed a written informed consent. Results: Mean age of HIV and CONTROL groups were 17.9 e 17.1 years, respectively. Postimmunization adverse events were similar in the two groups, but for pain, which was more intense in CONTROL group (20.0%x66.7%, p<0.001). On day 0, the percentage of susceptible individuals was comparable in both groups, although HIV group had higher tetanus antibody levels than CONTROL group. On days 14 and 28, both groups had an increase in tetanus, diphtheria and pertussis toxin antibodies. However, for diphtheria, HIV group had lower antibody levels on days 14 (p=0.001) and 28 (p=<0.001). Three individuals did not attain diphtheria protective antibody levels, and one of them did not seroconvert to tetanus as well. For pertussis, the percentage of individuals who seroconverted was significantly lower in HIV group on days 14 (p=0.002) and 28 (p=0.001). For the cellular immune response to tetanus, both groups built a Th2 (IL-4, IL-5 and IL-13) and Th1 (IFN-?) response. In HIV group, IL-17a levels increased; however, cytokine levels in supernatant were lower in HIV than in CONTROL group. In the cellular immune response to pertussis, HIV group had a statistically significant increase in Th1 (IFN-?) and Th17 (IL-17a) cytokines, while CONTROL group had an increase of Th2 (IL-4) cytokine. Conclusions: Antibody persistence for diphtheria and pertussis after primary vaccination scheme was similar in both groups. For tetanus, antibody levels were lowere in CONTROL than in HIV group, although the proportion of immune individuals was similar between groups. Both groups tolerated well Tdap. HIV and CONTROL groups presented an adequate humoral imune response to tetanus and diphtheria; however, HIV group had a lower seroconversion rate for pertussis than CONTROL group. Both HIV and CONTROL groups presented a cellular immune response to tetanus and pertussis. However, lower cytokine levels were observed in HIV group before and after Tdap, suggestive of a less efficient cellular response when compared to CONTROL group.